2016
DOI: 10.20892/j.issn.2095-3941.2016.0057
|View full text |Cite
|
Sign up to set email alerts
|

Implantable port thrombosis in cancer patients: a monocentric experience

Abstract: Objective:Implantable port thrombosis (IPT) in cancer patients is a relatively rare but severe complication. Several factors are reportedly associated with the occurrence of thrombosis. We aimed to describe the prevalence and the anatomoclinical features of IPT observed in cancer patients who were treated in a medical oncology department in Tunisia.Methods:A total of 600 cancer patients who had port implantation from January 2013 to December 2015 were retrospectively identified. Cases with symptomatic/incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 25 publications
0
13
1
2
Order By: Relevance
“…The rate of IVAD-related UEDVT is low at 1.29% (95% CI 0.2%-2.4%) in our study. Our reported rate of IVAD-related UEDVT seems lower than previously reported rates [8,10,16]. In a recent study including 600 cancer patients, 5.5% had IVAD-related DVT [16].…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…The rate of IVAD-related UEDVT is low at 1.29% (95% CI 0.2%-2.4%) in our study. Our reported rate of IVAD-related UEDVT seems lower than previously reported rates [8,10,16]. In a recent study including 600 cancer patients, 5.5% had IVAD-related DVT [16].…”
Section: Discussioncontrasting
confidence: 80%
“…Similarly, we reported a higher rate of IVAD-related UEDVT (4.5%, 95% CI, 2.5 to 6.3%) with a different IVAD. In both studies, the majority of patients were diagnosed with breast cancer or colorectal cancer [10,16]. A recently published prospective cohort study examining the rate of IVAD related VTE in 3032 patients across France found a rate of 3.8% [15].…”
Section: Discussionmentioning
confidence: 99%
“…First introduced in 1982, totally implanted venous access ports (TIVAPs) were extensively used in oncologic patients. These devices have been used as a safe method for avoiding venous injury and improving the quality of life for cancer patients (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Major complications after placement of the TIVAP include infection, thrombosis, catheter migration, occlusion, and central vein stenosis (6). Among these, venous thrombosis is the second major complication associated with TIVAPs after infection (5). Venous thrombosis caused by TIVAPs has been associated with high morbidity and additional costs (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation